Human-Nature Interactions 2022
DOI: 10.1007/978-3-031-01980-7_4
|View full text |Cite
|
Sign up to set email alerts
|

From Human-Nature Dualism Towards More Integration in Socio-ecosystems Studies

Abstract: Significance StatementIn the management of natural resources and biodiversity, humans and nature have traditionally been considered as two distinct systems, one controlling the other. The concept of socio-ecosystems allows a more integrated approach, in which humans and nature are recognized as interdependent. However, this new perspective does not necessarily eliminate a distinction between humans and nature, or even a hierarchy of humans over nature. This chapter aims to raise awareness of the potential huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…However, this asymmetric wording choice is imperfect in that it may seem to conjure an underlying asymmetric conception of the relationship between humans and nature. As noted by Boulangeat et al (2022), some SES may indeed reinforce the idea of hierarchy, with humans exploiting or protecting nature in an unidirectional way. This may be quite unintentional, and deeply grounded in an implicit belief system: Kluckhon and Strodtbeck (1961) suggested that any culture relies on one of three basic assumptions about the relationship between humans and nature, namely humans as dominant, as part of nature, or as subordinate to nature.…”
Section: Processes Of the Mtsesmentioning
confidence: 98%
“…However, this asymmetric wording choice is imperfect in that it may seem to conjure an underlying asymmetric conception of the relationship between humans and nature. As noted by Boulangeat et al (2022), some SES may indeed reinforce the idea of hierarchy, with humans exploiting or protecting nature in an unidirectional way. This may be quite unintentional, and deeply grounded in an implicit belief system: Kluckhon and Strodtbeck (1961) suggested that any culture relies on one of three basic assumptions about the relationship between humans and nature, namely humans as dominant, as part of nature, or as subordinate to nature.…”
Section: Processes Of the Mtsesmentioning
confidence: 98%